SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN PENERIMAAN REWARD PADA KARYAWAN CV. MODHECOM MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Diwi Apriana; Chandra Yuliansyah (Universitas Pahlawan Tuanku Tambusai, 2021)
Giving bonuses to employees is a form of appreciation given by a company, CV.Modhecom which is located in Bengkulu City currently has problems in providing rewards to its employees, sometimes in giving rewards only based on initial criteria, namely: attendance, years of service, attitude under pressure and discipline and in determining employee rewards are still manual, employees are not satisfied with receiving these rewards. Based on the existing problems, the researcher makes it easy to deal with problems by using the Decision Support System (DSS) method and in order to be able to assist in calculating all the criteria when making a decision, the Simple Additing Weighting (SAW) method is used. After that, so that this research can run on CV. Modhecom then tested users by distributing questionnaires to higher-ups who usually gave an assessment of employees, at the stage of testing the quality of the system researchers used Black-Box testing and the results of hypothesis testing using the TAM model, so that it could be seen how influential the respondents were on convenience, usability and acceptance of the system that has been created. In this study, after testing, it provides convenience results for CV. Modhecom with the evidence that the effect of receiving rewards with the system made reaches 10.4%.